Laser Nano-Neurosurgery from Gentle Manipulation to Nano-Incision of Neuronal Cells and Scaffolds: An Advanced Neurotechnology Tool - Soloperto, Alessandro; Palazzolo, Gemma; Tsushima, Hanako; Chieregatti, Evelina; Vassalli, Massimo; Difato, Francesco (Frontiers in Neuroscience, 2016)
Current optical approaches are progressing far beyond the scope of monitoring the structure and function of living matter, and they are becoming widely recognized as extremely precise, minimally-invasive, contact-free handling tools. Laser manipulation of living tissues, single cells or even single-molecules is becoming a well-established methodology, thus founding the onset of new experimental paradigms and research fields. Indeed, a tightly focused pulsed laser source permits complex tasks such as developing engineered bioscaffolds, applying calibrated forces, transfecting, stimulating or even ablating single cells with subcellular precision, and operating intracellular surgical protocols at the level of single organelles. In the present review, we report the state of the art of laser manipulation in neuroscience, to inspire future applications of light-assisted tools in nano-neurosurgery.